Antioxidative activities and polyphenolic content of different varieties of Malaysian young corn ear and cornsilk - Ho, Y.M.; Wan Amir Nizam W.A.,; Wan Rosli W.I., (Universiti Kebangsaan Malaysia, 2016)
This study aimed to determine the antioxidant capacity, total polyphenolic and total flavonoid content of Malaysian young corn ear (YCE) and its cornsilk (CS) of different varieties. Three different varieties of YCE and its CS locally grown in Malaysia were chosen namely Big Fruit, Thai Supersweet and Bi-color. CS Bi-color displayed the highest total phenolic content (143.58 mg GAE/g extract) while CS Thai Supersweet exhibited the highest total flavonoid content (26.63 mg CAE/g extract). Meanwhile, YCE of Bi-color variety demonstrated the highest total polyphenolic and flavonoid content (92.64 and 18.14 mg CAE/g extract, respectively) compared to other YCE varieties. At 800 µg/mL, CS of Bi-color (93.82%) recorded the strongest electron donor due to higher DPPH scavenging activity, followed by CS Thai Supersweet (92.87%), YCE Bi-color (41.94%), YCE Thai Supersweet (28.87%), CS Big Fruit (28.87%) and YCE Big Fruit (21.38%). For FRAP, CS of Bi-color showed the highest reducing power activity (65.46%) among all the crude extracts. There is a significant correlation between total polyphenolic content, DPPH free radical scavenging activity and FRAP of YCE and CS of different varieties. In summary, CS extracts are the potential ingredient to be applied in food industries and at the same time reducing agriculture wastage.